2023
DOI: 10.13057/biodiv/d240537
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and structure of Eurycoma longifolia habitat in Muka Kuning Nature Tourism Park, Riau Islands, Indonesia

Abstract: Abstract. Susilowati A, Rachmat HH, Yulita KS, Wijaya K. 2023. Floristic composition and structure of Eurycoma longifolia habitat in Muka Kuning Nature Tourism Park, Riau Islands, Indonesia. Biodiversitas 24: 2836-2842. Eurycoma longifolia Jack, locally called as pasak bumi,is a popular medicinal plant which is known to have properties in curing various diseases. The root of E. longifolia is the organ that has the highest aphrodisiac content so hunting for the roots of E. longifolia destructively causes a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Dipterocarpus rigidus grows and distributes naturally in lowland tropical forests at altitudes of less than 200 m asl as reported by Brearley et al (2007), who discovered D. rigidus growing in hilly forest areas at an elevation of around 150 m asl in Central Kalimantan. Meanwhile, previous studies reported D. rigidus grows naturally at low altitudes (100 m asl) in Riau and Batam Island (Subiakto et al 2016;Susilowati et al 2023). This species is a large-size tree with cylindrical trunk and is distinguished by a yellowish-green crown when viewed from below (Subiakto et al 2016).…”
Section: Floristic Composition In Sei Harapan Protection Forestmentioning
confidence: 96%
See 1 more Smart Citation
“…Dipterocarpus rigidus grows and distributes naturally in lowland tropical forests at altitudes of less than 200 m asl as reported by Brearley et al (2007), who discovered D. rigidus growing in hilly forest areas at an elevation of around 150 m asl in Central Kalimantan. Meanwhile, previous studies reported D. rigidus grows naturally at low altitudes (100 m asl) in Riau and Batam Island (Subiakto et al 2016;Susilowati et al 2023). This species is a large-size tree with cylindrical trunk and is distinguished by a yellowish-green crown when viewed from below (Subiakto et al 2016).…”
Section: Floristic Composition In Sei Harapan Protection Forestmentioning
confidence: 96%
“…The existence of Dipterocarpaceae species on this island has been widely reported, including by Subiakto and Rachmat (2015), Susilowati et al (2020), Subiakto et al (2016) and Susilowati et al (2023) including Dipterocarpus rigidus. Although recent study evidence indicates that this species still persists its natural habitat (Susilowati et al 2023), the IUCN Red List classifies D. rigidus as Critically Endangered (Rachmat et al 2020) and is listed in Appendix I CITES, implying that the trade of this species is prohibited. It also indicates that various types of disturbances have resulted in a significant decrease in D. rigidus population, posing a serious threat to its long-term viability.…”
Section: Introductionmentioning
confidence: 95%